If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 + -3x = 24x + 16 Reorder the terms: 52 + -3x = 16 + 24x Solving 52 + -3x = 16 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 52 + -3x + -24x = 16 + 24x + -24x Combine like terms: -3x + -24x = -27x 52 + -27x = 16 + 24x + -24x Combine like terms: 24x + -24x = 0 52 + -27x = 16 + 0 52 + -27x = 16 Add '-52' to each side of the equation. 52 + -52 + -27x = 16 + -52 Combine like terms: 52 + -52 = 0 0 + -27x = 16 + -52 -27x = 16 + -52 Combine like terms: 16 + -52 = -36 -27x = -36 Divide each side by '-27'. x = 1.333333333 Simplifying x = 1.333333333
| 1+x^4-2x^2+1.96x^2=1.0096x^4 | | -6x+7=10-5x | | 60+.6x=.8x | | (w+8)(w-3)=0 | | 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 | | y=5-8x | | 12x-10=4x-5 | | 2x+3=33+7x | | (-3y^2-8y)+(6y^2+y-9)= | | 18(4/9) | | -4/7+2/5u=-1/2 | | -4+7x=x+20 | | 9x+6=3x-2 | | 5(8)+8y=40 | | x*x+6x+c= | | 6y^2+11=4y | | 10/15x=8 | | X/8=x+3/20 |